Identification of Design Variables for a Supply Chain Risk Management Audit - Meike Schröder; Johannes Beck; Wolfgang Kersten (Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 20, 2015)
Due to an increasing vulnerability in today's supply chains a supply chain risk management (SCRM) system is strongly recommended, especially for companies with a high degree of dependence on supply chain partners. However, as a permanent and effective use of the SCRM system is not only ensured by a successful implementation, an appropriate control mechanism needs to be implemented. Auditing the SCRM system can be such a solution. The main objective of this study is the identification of variables and their possible design related to SCRM systems. Based on an extensive literature review aiming to identify those variables, an empirical study with experts in the field of auditing is carried out. The transmission of the results to the concept of SCRM leads to possible configurations of the variables, both for a general internal SCRM self-audit and an audit focused on small and medium sized enterprises (SME).
10419/209189; https://econpapers.repec.org/RePEc:zbw:hiclpr:20
Keywords: 650; Supply Chain Risk Management; Supply Chain Management; Auditing; SME